Um olhar sobre a documentação de performances não institucionalizadas: estudo de caso de “Memória do afeto” de Beth Moysés e “Esmagamento sensível” de Marco Paulo Rolla - Juliana Pereira Sales Caetano (2024)
In Brazil, over the past few decades, the presence of performative works in art fairs, galleries, salons, biennials, and both public and private collections has grown and become increasingly noticeable. Conversely, there is a need to optimize preservation guidelines concerning documentation protocols for this language. This is because it is common to find performances in museum collections with numerous informational gaps, many of which originate in the acquisition process. In this regard, this thesis aims to present proposals for guidelines to complement the documentation produced by artists, aiming to facilitate future acquisition. It emphasizes the relevance of considering the characteristics of each performance, which has a significant impact especially at the time of a reactivation. To illustrate, the performances “Memória do Afeto” [Memory of Affection] by Beth Moysés and “Esmagamento Sensível” [Sensitive Crushing] by Marco Paulo Rolla are presented, which display distinct conceptual and immaterial aspects. For suggesting documentation protocols, the intentionality of the artists was considered in aspects such as: reactivation, acquisition, materiality, interaction with the public, documents of the action, relationship with space, and context. Methodological procedures included research in secondary sources, such as theoretical reviews from national and international references in the fields of Conservation and Restoration of Movable Goods, Art History, Museology, among other fields of knowledge; in addition to research on other works of art. Primary sources include consulting the artists' archives on the course and the versions of the performances.